The adoption of Customer Relationship Management (CRM): an empirical study on Iranian firms. (19th June 2008) - Keramati, A.; Zavareh, J. Toufighi; Ellioon, A.; Moshki, H.; , S. Sajjadiani
To state the Customer Relationship Management (CRM) adoption by Iranian firms, CRM practices are empirically investigated in this research. For this purpose, a survey in 41 Iranian firms of five different business sectors has been conducted. Differences of CRM usage, among firms from various sectors, have been analysed. The results show that investigated organisations are adopting CRM in some limited extent, which could lead to hinder them from fully utilising the potentials of such systems. Researchers, strategic managers and CRM vendors can find a set of useful information about the state of CRM usage in Iranian organisations in this paper.